IMPACT OF DIFFERENT FACTORS ON THE FARMERS DECISION TO INSURE CROP PRODUCTION - Miljatović, Aleksandar; Tekić, Dragana; Vukoje, Veljko; Novaković, Tihomir; Marković, Todor (Economics of Agriculture, 2021)
The aim of the paper is to consider and analyze the impact of subsidies levels and other economic and general factors on the farmers decision to insure their crops. The paper applies the model of logistic regression in order to determine the statistically significant influence of certain factors on the decision of farms. The subject of the research is general and economic data from agricultural holdings in the FADN sample in Serbia for 2018. The sample includes farms that deal with specialist field crops, specialist grazing livestock and mixed crops-livestock production. The survey was conducted on a sample of 819 households, of which 99 households reported insurance costs (12.1%). The results of the research show that with higher subsidy level the probability that farms will insure their production reduces. On the other hand, with an increase of economic size and farm net value added per annual working unit the probability that farms will be insured also increases.